Έργα και ημέρες ενός διαβόητου συκοφάντη (;) στην Αθήνα του 4ου αι. π.Χ.: Θεοκρίνης Υβάδης - Μπαρτζώκα Αλεξάνδρα (Tekmeria, 2024)
Theocrines was a well-known sycophant who often brought false charges against his fellow citizens in the hope of profiting financially. This is what Epichares asserts in his oration Against Theocrines, delivered ca. 343-338 BCE, in order to avenge his father. Theocrines had earlier charged and successfully prosecuted Epichares’ father for proposing an illegal decree. This led Epichares to bring a denunciation against Theocrines, claiming that his adversary had violated numerous laws on several occasions. Apart from this speech, two epigraphic testimonies also provide biographical details about Theocrines. These inscriptions suggest that, following his trial, he took on public offices as a public arbitrator and councillor. This article aims to combine these different aspects of Theocrines’ life and challenge the negative and stereotypical depiction of him as a notorious sycophant. This portrayal has been predominant in modern studies primarily because they heavily rely on Epichares’s speech alone. Hence, the critical question arises whether this speech delivered by a vindictive Epichares can be taken literally to draw reliable conclusions about the reprehensible practices attributed to Theocrines. Characterizing Theocrines solely as a sycophant is debatable and only represents one facet of his public life. Thus, by examining these varied sources, we can develop certain hypotheses about Theocrines’ character, the substance of Epichares’ claims, and the workings of Athenian democracy.